2021
DOI: 10.1136/bmjgh-2020-004064
|View full text |Cite
|
Sign up to set email alerts
|

Multisectoral action for health in low-income and middle-income settings: how can insights from social science theories inform intragovernmental coordination efforts?

Abstract: There is consensus in global health on the need for multisectoral action (MSA) to address many contemporary development challenges, but there is limited action. Examples of issues that require coordinated MSA include the determinants of health conditions such as nutrition (malnutrition and obesity) and chronic non-communicable diseases. Nutrition, tobacco control and such public health issues are regulated separately by health, trade and treasury ministries. Those issues need to be coordinated around the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 71 publications
2
29
0
Order By: Relevance
“…By illuminating the donors' power in shaping the development agenda over the last three decades, this study underscores a context particular to donor-dependent LMICs, and a period when certain donors pushed for institutional strengthening of MDAs as a way to bolster ('good') governance. 65 83 Applying a multitheoretical approach: reflections and implications This paper contributes to the literature on theory building and, more specifically, applying a multitheoretical approach to research 84 85 and examines the empirical relevance of the multitheoretical framework proposed by Ssennyonjo et al 12 This work contributes to studies that have used theories to analyse data and interpret findings. 33 36 37 86 We demonstrated how a multitheoretical approach is particularly pertinent to intragovernmental coordination.…”
Section: Coordination-related Transaction Costsmentioning
confidence: 96%
See 2 more Smart Citations
“…By illuminating the donors' power in shaping the development agenda over the last three decades, this study underscores a context particular to donor-dependent LMICs, and a period when certain donors pushed for institutional strengthening of MDAs as a way to bolster ('good') governance. 65 83 Applying a multitheoretical approach: reflections and implications This paper contributes to the literature on theory building and, more specifically, applying a multitheoretical approach to research 84 85 and examines the empirical relevance of the multitheoretical framework proposed by Ssennyonjo et al 12 This work contributes to studies that have used theories to analyse data and interpret findings. 33 36 37 86 We demonstrated how a multitheoretical approach is particularly pertinent to intragovernmental coordination.…”
Section: Coordination-related Transaction Costsmentioning
confidence: 96%
“…Consistent with PE perspectives and RDT, the findings confirm that these costs could be positively mediated by trust, considerations of what interdependence entails, a communication strategy and earmarked budgets for coordination. 12 The political nature of coordination The study revealed several manifestations of power dynamics, including competition and conflicts over resources (especially budgets), donor inducing compliance through conditioning coordination on aid, contestations over mandates, framing issues in self-interested ways and adopting behaviours (such as non-compliance to rules) to undermine the power of coordinating agencies. Consistent with the PE literature, 60 68 informal norms of demanding teas and transport allowances and instances of corruption, such as misappropriation of funds, were documented.…”
Section: Coordination-related Transaction Costsmentioning
confidence: 99%
See 1 more Smart Citation
“…Health (and illness) results from actions taken by individuals, communities, corporations, and governments within and, crucially, outside the health sector. The same logic applies to planetary health16 with health, business, and environment literature reporting similar barriers to, and facilitators of, intersectoral action 171819202122. We conducted a pragmatic review, grouping the wide variety of barriers and opportunities described into seven themes (box 3).…”
Section: Barriers and Facilitators To Intersectoral Actionmentioning
confidence: 88%
“…Filho et al [ 40 ] reported that only few studies in the literature have explored PA interventions in LMICs, mainly noting the importance of school-based, multicomponent interventions. More studies have rather explored multisectoral approaches involved in the promotion of PA related outcomes such as NCDs and general health in LMICs [ 39 , 41 , 42 , 43 ]. The multisectoral nature of PA is exemplified in the 2018–2023 Kenyan National Physical Activity Plan, led by the Kenyan Ministry of Health.…”
Section: Discussionmentioning
confidence: 99%